Idiopathic Chronic Eosinophilic Pneumonia Evolving to Pulmonary Fibrosis: A Retrospective Analysis: Eosinophilic Pneumonia and Fibrosis - Baqir, Misbah; Peikert, Tobias; Johnson, Tucker; Tandon, Yasmeen; Yi, Eunhee; Schroeder, Darrell; Ryu, Jay (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2022)
Background: Patients with idiopathic chronic eosinophilic pneumonia (ICEP) may have pulmonary fibrosis.Objectives: To investigate the predictors of pulmonary fibrosis in ICEP, to describe the timeline of pulmonary fibrosis after ICEP diagnosis, and to detail the radiologic pattern of fibrosis.Methods: A retrospective computer-assisted search was performed to identify patients with ICEP seen at Mayo Clinic in Rochester, Minnesota from January 1, 1997, through September 1, 2019. Patients with follow-up chest computed tomography (CT) beyond 12 months after the ICEP diagnosis were included in the study. Demographic, clinical, radiologic, and histopathologic characteristics were analyzed. Proportional hazards regression was used to assess the predictors of pulmonary fibrosis.Results: We identified 62 patients (mean [SD] age at ICEP diagnosis, 60 [13] years; female sex, 37 [60%]). Cough (87%) and shortness of breath (85%) were the most common presenting symptoms. Of patients, 27 (44%) had a history of smoking and 27 (44%) had a history of asthma. During follow-up, 23 patients (37%) had CT evidence of pulmonary fibrosis, of whom 16 patients (70%) had a CT pattern inconsistent with usual interstitial pneumonia. In 29% of the patients, the CT evidence of pulmonary fibrosis developed within 2 years after ICEP. Age and male sex were predictors of pulmonary fibrosis. Of note, a history of asthma decreased the likelihood of pulmonary fibrosis.Conclusions: Development of pulmonary fibrosis is not uncommon in patients with ICEP, especially older men, and is associated with increased risk of death.